Using the Bridge21 pedagogical model of 21st century teaching and learning to teach new literacies in second-level English education, and the impact on students' attitudes - Kearney, Sharon (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2018)
The development and proliferation of 21st century (21C) information and communication technology (ICT) has enabled new ways of reading, writing and communicating. These new or 21C literacies are concurrently digital, multimodal and collaborative, and they require new skills. Second-level English education is aiming to adjust to include these new literacies in order to engage students more in the learning process and to develop students' key new literacy skills for today’s economy and society and for future. However, two main problems related to implementing changes are present. First, there is limited understanding of how and why teaching new literacies impacts students’ attitudes in English, as relatively few studies in this area have been conducted. Technology and the new literacies enabled by ICT are only as powerful as the approaches in which they are used, yet fewer studies investigate pedagogies for effectively teaching new literacies in English education. Second, English teachers report needing guidance in how to teach new literacies effectively: to engage students, meet curricular aims, and/or develop their students’ literacy skills. This dissertation presents research which sought to address these issues. It was hypothesised that the Bridge21 pedagogical model for 21st Century (21C) teaching and learning - a technology-mediated, team-based and project-based approach - could be adapted and utilised as a framework for teaching new (21C) literacies in second-level English education. To investigate the effectiveness of this approach, students' attitudes (engagement and confidence) in English skills and content were primarily considered. A methodological approach that utilised both case studies and elements of action research was employed. The research design involved three phases: (1) an exploratory case study with students, to design and pilot learning interventions, develop data collection tools, and refine analysis procedures; (2) an explanatory case study with students, to analyse the impact of this adaptation of the Bridge21 approach for teaching new literacies on students' attitudes in English; and (3) an exploratory case study with teachers investigating their experiences using the approach in English classes. Both qualitative and quantitative methods were employed to answer the research questions. The results showed significant positive changes in students' engagement and confidence in English following the learning interventions, suggesting Bridge21 can be an effective pedagogy for teaching new literacies in the English education context. Contributions of this research include: a deeper understanding of how and why a particular pedagogical approach to teaching new literacies impacts students' attitudes; the development of a validated quantitative tool (the ETAS) to measure the effects of technology-mediated learning interventions on students' attitudes in English; a pedagogical approach, Bridge21, for effectively teaching new literacies; and the sharing of the approach and resources with teachers, and a preliminary investigation into their experiences of using them in their classrooms.
APPROVED
Keywords: English education; new literacies; technology-mediated learning; 21C teaching and learning; second-level; adolescent